2019
DOI: 10.7554/elife.52384
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing human antibodies against dengue virus identified by single B cell transcriptomics

Abstract: Eliciting broadly neutralizing antibodies (bNAbs) against the four dengue virus serotypes (DENV1-4) that are spreading into new territories is an important goal of vaccine design. To define bNAb targets, we characterized 28 antibodies belonging to expanded and hypermutated clonal families identified by transcriptomic analysis of single plasmablasts from DENV-infected individuals. Among these, we identified J9 and J8, two somatically related bNAbs that potently neutralized DENV1-4. Mutagenesis studies showed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 113 publications
7
70
0
Order By: Relevance
“…It was also demonstrated that distinct dengue-infected individuals develop variable titers of antibodies that recognize a specific neutralizing epitope ( 85 ). Two recent studies identified and characterized the functional activity and B-cell lineage of broadly neutralizing dengue antibodies ( 72 ) and demonstrated that activated, clonally expanded T cells that become committed to the dengue repertoire have a unique transcriptional signature ( 86 ). More specifically, this last study applied single-cell RNA sequencing on T-cell receptor (TCR) immune repertoires.…”
Section: Large-scale Immune Repertoire Sequencing To Study the Dengue Immune Responsementioning
confidence: 99%
“…It was also demonstrated that distinct dengue-infected individuals develop variable titers of antibodies that recognize a specific neutralizing epitope ( 85 ). Two recent studies identified and characterized the functional activity and B-cell lineage of broadly neutralizing dengue antibodies ( 72 ) and demonstrated that activated, clonally expanded T cells that become committed to the dengue repertoire have a unique transcriptional signature ( 86 ). More specifically, this last study applied single-cell RNA sequencing on T-cell receptor (TCR) immune repertoires.…”
Section: Large-scale Immune Repertoire Sequencing To Study the Dengue Immune Responsementioning
confidence: 99%
“…However, it is too early to reject the hypothesis that vaccination with COVID-19 vaccines barely cause ADE. Researches indicated ADE could happen at sub-neutralizing concentrations of the antibodies when cells were infected by HIV-1, DENV or Enterovirus 71 (EV71) (Chen et al 2013;Durham et al 2019;Meyer et al 2011). With the weaning on immune response induced by current vaccination program of COVID-19 vaccines, there is stubborn potential of ADE caused when immunized people is infected by SARS-CoV-2.…”
Section: Vaccine-associated Disease Enhancement (Vade)mentioning
confidence: 99%
“…Durham et al . previously used transcriptomic analysis and identified novel recognition determinants of bNAbs within the DENV EDI region 41 .…”
Section: Mbc and Antibody Responses To Flavivirus Infection And Vaccimentioning
confidence: 99%